Field Measurements in Determining Incumbent Spectrum Utilization and Protection Criteria in Wireless Co-existence Studies - Kalliovaara, Juha (fi=Turun yliopisto|en=University of Turku|, 2017)
Studies of spectrum sharing and co-existence between diﬀerent wireless communication systems are important, as the current aim is to optimize their spectrum utilization and shift from static exclusive spectrum allocation to more dynamic co-existence of diﬀerent systems within same frequency bands. The main goal of this thesis is to provide measurement methodologies for obtaining realistic results in modeling incumbent spectrum utilization and in determining incumbent protection criteria. The following research questions are considered in this thesis: Q1) How should ﬁeld measurements be conducted and used to model incumbent spectrum utilization? Q2) How should ﬁeld measurements be conducted and used to determine protection criteria for incumbents in a co-existence scenario with mobile broadband? and Q3) Which licensing methods and technological solutions are feasible to enable spectrum sharing in frequency bands with incumbents? To answer to Q1, this thesis describes the development of a spectrum observatory network concept created through international collaboration and presents measurement methodologies, which allow to obtain realistic spectrum occupancy data over geographical areas using interference map concept. A cautious approach should be taken in making strong conclusions from previous single ﬁxed location spectrum occupancy studies, and measurements covering larger geographical areas might be needed if the measurement results are to be used in making spectrum management decisions. The ﬁeld interference measurements considered in Q2 are not covered well in the current research literature. The measurements are expensive to conduct as they require substantial human resources, test network infrastructure, professional level measurement devices and radio licenses. However, ﬁeld measurements are needed to study and verify hypotheses from computer simulations or theoretical analyses in realistic operating conditions, as ﬁeld measurement conditions can not or are not practical to be adequately modeled in simulations. This thesis proposes measurement methodologies to obtain realistic results from ﬁeld interference measurements, taking into account the propagation environments and external sources of interference. Less expensive simulations and laboratory measurements should be used both to aid in the planning of ﬁeld measurements and to complement the results obtained from ﬁeld measurements. Q3 is investigated through several ﬁeld interference measurement campaigns to determine incumbent protection criteria and by analyzing the spectrum observatory data to determine the occupancy and trends in incumbent spectrum utilization. The ﬁeld interference measurement campaigns have been conducted in real TV White Space, LTE Supplemental Downlink and Licensed Shared Access test network environments, and the obtained measurement results have been contributed to the development of the European spectrum regulation. In addition, ﬁeld measurements have been conducted to contribute to the development and technical validation of the spectrum sharing frameworks. This thesis also presents an overview of the current status and possible directions in spectrum sharing. In conclusion, no single spectrum sharing method can provide universally optimal eﬃciency in spectrum utilization. Thus, an appropriate spectrum sharing framework should be chosen taking into account both the spectrum utilization of the current incumbents and the future needs in wireless communications.